Dynamics Model of Chickenpox with Effect of the Mass Media - Wongwiwat, Piyada; ., . (International Journal of Engineering and Technology, 2018)
In this paper, an SIR model (Susceptible – Infectious – Recovered) analyze the Chickenpox transmission by considering the effect of mass media to understand the dynamic of the disease in Thailand. This dynamical model is analyzed using a standard dynamical modeling method. The stability of the model was determined by using Routh-Hurwitz criteria. In this paper, the disease free and endemic state have been found. To determine the basic reproductive number (R0) which is the threshold parameter, if R0 <1, the disease free equilibrium point is locally asymptotically stable. The result shows that the mass media significantly cause the reduction in transmission and infection of Chickenpox in Thailand. So, the mass media may be another option to prevent and control the disease.